2023
DOI: 10.2903/j.efsa.2023.6857
|View full text |Cite
|
Sign up to set email alerts
|

Re‐evaluation of the risks to public health related to the presence of bisphenol A (BPA) in foodstuffs

Abstract: In 2015, EFSA established a temporary tolerable daily intake (t‐TDI) for BPA of 4 μg/kg body weight (bw) per day. In 2016, the European Commission mandated EFSA to re‐evaluate the risks to public health from the presence of BPA in foodstuffs and to establish a tolerable daily intake (TDI). For this re‐evaluation, a pre‐established protocol was used that had undergone public consultation. The CEP Panel concluded that it is Unlikely to Very Unlikely that BPA presents a genotoxic hazard through a direct mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(77 citation statements)
references
References 845 publications
(2,989 reference statements)
0
51
0
Order By: Relevance
“…Its use in food containers is banned in France but still under discussion at the EU level. In 2023, EFSA re-evaluated tolerable daily intake of BPA in food containers from 4 mg/kg/day to 0.2 ng/kg/day (EFSA, 2023). Use of phthalates such as di(2-ethylhexyl) phthalate (DEHP), dibutyl phthalate (DBP), benzyl butyl phthalate (BBP), diisobutyl phthalate (DIBP), must be less than 0.1% in electrical and electronic equipment, toys and childcare articles.…”
Section: Introductionmentioning
confidence: 99%
“…Its use in food containers is banned in France but still under discussion at the EU level. In 2023, EFSA re-evaluated tolerable daily intake of BPA in food containers from 4 mg/kg/day to 0.2 ng/kg/day (EFSA, 2023). Use of phthalates such as di(2-ethylhexyl) phthalate (DEHP), dibutyl phthalate (DBP), benzyl butyl phthalate (BBP), diisobutyl phthalate (DIBP), must be less than 0.1% in electrical and electronic equipment, toys and childcare articles.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, human exposure to bisphenols can occur through inhalation, ingestion, and dermal contact. , Previous studies categorized the Northeast Indian population into three groups based on environmental phenol concentrations in urine samples, allowing for analysis of associations with health outcomes . In pregnant women, BPA was found to be present in urine samples during the first and second trimesters at concentrations of 1.39 and 1.27 ng/mL, respectively, as reported by Chiu et al Additionally, similar to BPA, the presence of bisphenol F (BPF) and bisphenol AF has been detected in human urine, blood, and adipose tissue in studies. The European Food Safety Authority (EFSA) has defined a tolerable daily intake (TDI) for BPA at 0.2 ng/kg body weight per day . Recent studies have demonstrated the detrimental effects of BPA and its structural congeners, including bisphenol AF, bisphenol G, bisphenol M, and bisphenol X, on microalgae species like Chlorella vulgaris and Desmodesmus armatus .…”
Section: Introductionmentioning
confidence: 79%
“…via continuous determination of tolerated intake doses (TDI). For instance, just very recently the EFSA (European Food Safety Authority) proposed a TDI of 0.2ng/kg body weight/day for bisphenol A (BPA) illustrating the need for continuous research of potential health implications in order to control exposure to hazardous substances [22].…”
Section: Bisphenolsmentioning
confidence: 99%